Inappropriate prescribing in hospitalized elderly patients - Massoud, Lina K.; AlAgha, Hala Z.; Taleb, Mahmoud H. (International Journal of Basic & Clinical Pharmacology, 2017)
Inappropriate prescribing (IP) is a major healthcare problem in elderly patients. The risk of this problem increases during hospitalization. This is due to increase morbidity and thus increases the use of medications by the inpatients. This study will clarify the problem of IP for elderly people during hospitalization and will identify the different types of it. It also will highlight some tools that are used to assess the different types of IP and the prevalence of it in elderly patients during hospitalization. Finally, the study will address the consequences of IP in the elderly inpatients and the risks associated with the use of some potentially inappropriate medications (PIMs) in the elderly.